수소에너지에 대한 ISO 표준화 동향과 시사점 - 김종원(Jong-won Kim); 이택홍(Taeck Hong Lee); 최재우(Jae-woo Choi) (한국수소 및 신에너지학회 논문집, 2016)
Commercial production line of FCEV was built in 2013 by Hyundai and followed by Toyota in 2014, with additional manufacturers planning to enter the market around 2017. Now there is limited hydrogen infrastructure over the world, but more hydrogen stations are planned, particularly in Japan, Korea, Germany, UK and USA. ISO TC 197 which was created in 1990 focused standardization in the field of systems and devices for the production, storage, transport, measurement and use of hydrogen. Total number of published ISO standards related to the TC and its SCs (number includes updates) is 17. Now there are 20 participating countries and 13 observing countries. The current status of activity of ISO TC197 was reviewed and particularly issues on hydrogen quality and hydrogen refueling station were discussed.